Frequency of Dyslipidemia in Patients Having Subclinical Hypothyroidism - Mehwash Iftikhar; Mian Mufarih Shah; Nazeer Shah; Bilal Khattak; Imran Khan; Sheraz Jamal Khan (Gandhara University, 2024)
OBJECTIVES To determine the lipid abnormalities in subclinical hypothyroidism. METHODOLOGY A case-control study was conducted on euthyroid and subclinical hypothyroid patients presenting to OPD and medical wards of Hayatabad Medical Complex from January to December 2023. The euthyroid control arm had no history of thyroid disease in the past. These hundred control patients were compared to a hundred cases who had subclinical hypothyroidism. All the patients underwent laboratory tests for thyroid hormones and lipid levels. Overt hypothyroidism was excluded. All the results were compared using SPSS statistical analysis version 23. RESULTS We found that in subclinical hypothyroidism, high triglycerides (TG) were the only abnormal findings, while total cholesterol (TC) and high-density lipoproteins (HDL) were not affected. The risk of hyper triglyceridemia with thyroid stimulating hormone (TSH) levels ≥10mIU/L was 2-fold higher compared to that in the average population (P<0.05).. CONCLUSION Disorders of TG metabolism with subclinical hypothyroidism show a direct correlation with the level of TSH, and the risk of hypertriglyceridemia is moderately increased when the level of TSH ≥10mIU/L. SCH does not affect the level of TC and HDL.